The Pivotal Issues of Human Rights: A Literature Review by Eight World Researchers - Hidayati Hidayati; Achmad Nur Sutikno; Sandra Erawanto (Jurnal Studi Sosial dan Politik, 2022)
The aim of this study was to investigate the studies of eight human rights researchers. The methodology used is a systematic mapping study on the literature on human rights with sources from reputable journals in the world. The result of this study is that eight researchers contributed to the human rights literature review. The impact of that is to increase the level of literature review in various aspects and objects of research. Further research suggestions are to look for state of the art research.